Hospital and Temple: 1291‒1314 - Luttrell, Anthony (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2025)
When the fall of Acre in 1291 led to the loss of their powerful position in Syria the military-religious orders of the Hospital and Temple had to adjust to a restricted establishment on Cyprus. The two orders had much in common but they also displayed significant differences. The Hospital intervened in defence of Cilician Armenia; the Templars looked to the recuperation of Jerusalem, a policy which led to a military disaster on the islet of Ruad off Tortosa in 1302. Scholarly attention is often centred on the long-serving Templar Master Jacques de Molay and his order’s suppression, an astonishing quasi-accidental event in which between 1307 and 1312 the French king, Philippe IV, exploited the Temple’s institutional weaknesses to attack the papacy. The Hospitals’ government was more balanced and in 1306 its astute Master Foulques de Villaret invaded Rhodes, where the Hospital began the creation of a defensible island “order state.” Pope Clement V, together with Villaret, blocked King Philippe’s assaults and the papacy and the Hospital survived to sustain a measure of holy warfare, while the Hospital gained the bulk of the Temple’s possessions. The price was the destruction of the Temple. ACKNOWLEDGEMENT: Karl Borchardt, Marie-Anna Chevalier, and Nicholas Coureas kindly provided invaluable assistance.